Mesenteric panniculitis: can venous anatomy and malignancy be a trigger cause? - Gültekin, Mehmet Ali (The European Research Journal, 2021)
Objectives: To investigate whether portal vein (PV), splenic vein (SV), superior mesenteric vein (SMV) diameters and portomesenteric angle (PMA) may play a role in the etiology of mesenteric panniculitis (MP). To investigate relationship between MP and malignancy. Methods: We included 70 patients with MP and 70 patients age, gender, sagittal abdominal diameter randomly matched control group, retrospectively. Results: We found slightly higher PV and SMV diameter and slightly lower SV diameter in MP patients compared with control group. But these results were not statistically significant (p1 = 0.321 and p2 = 0.147, p1 = 0.540 and p2 = 0.185, p1= 0.216 and p2 = 0.617, for two observers respectively). We found higher PMA in MP patients compared with control group but this difference is not statistically significant (p1 = 0.252 and p2 = 0.366, for two observers). Twenty three (32.9%) of 70 patients diagnosed MP have underlying malignancy while 17 (24.3%) of 70 control subject were coexisted malignancy. But this difference is not statistically significant (p = 0.262). Interobserver agreement was excellent in terms of SMV and SV diameters and PMA measurements (ICC were 0.927, 0.911 and 0.965 respectively), good for PV diameters (ICC was 0.884). Conclusions: Study results show that MP is not associated with PV, SMV and PMA. Contrary to some studies, there is no relationship between MP and malignancy.